2023
DOI: 10.1055/s-0043-1768580
|View full text |Cite
|
Sign up to set email alerts
|

Visit-to-Visit Heart Rate Variability in the Prediction of Clinical Outcomes of Patients with Atrial Fibrillation

Abstract: Background Visit-to-visit heart rate variability (VVV-HR) has been associated with adverse cardiovascular outcomes. We aimed to determine the predictive value of VVV-HR for adverse clinical outcomes in patients with nonvalvular atrial fibrillation (AF). Methods We used data from a prospective multicenter AF registry of 27 hospitals in Thailand during 2014 to 2017. After the baseline visit, patients were followed up every 6 months until 3 years. VVV-HR was calculated from the standard deviation of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…This conclusion is similar to our study, which found a U-shaped relationship between VVHRV and all-cause mortality. Another recent study (Krittayaphong et al, 2023), conducted with data from multiple centers in Thailand, revealed that VVHRV is an independent predictor of poor prognosis in patients with AF. VVHRV exhibits a J-curve effect on allcause mortality in that study.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is similar to our study, which found a U-shaped relationship between VVHRV and all-cause mortality. Another recent study (Krittayaphong et al, 2023), conducted with data from multiple centers in Thailand, revealed that VVHRV is an independent predictor of poor prognosis in patients with AF. VVHRV exhibits a J-curve effect on allcause mortality in that study.…”
Section: Discussionmentioning
confidence: 99%